Hydrogen-powered aviation and its reliance on green hydrogen infrastructure – Review and research gaps. (15th January 2022) - Hoelzen, J.; Silberhorn, D.; Zill, T.; Bensmann, B.; Hanke-Rauschenbach, R.
Abstract: Aircraft powered by green hydrogen (H2) are a lever for the aviation sector to reduce the climate impact. Previous research already focused on evaluations of H2 aircraft technology, but analyses on infrastructure related cost factors are rarely undertaken. Therefore, this paper aims to provide a holistic overview of previous efforts and introduces an approach to assess the importance of a H2 infrastructure for aviation. A short- and a medium-range aircraft are modelled and modified for H2 propulsion. Based on these, a detailed cost analysis is used to compare both aircraft and infrastructure related direct operating costs (DOC). Overall, it is shown that the economy of H2 aviation highly depends on the availability of low-cost, green liquid hydrogen (LH2) supply infrastructure. While total DOC might even slightly decrease in a best LH2 cost case, total DOC could also increase between 10 and 70% (short-range) and 15–102% (medium-range) due to LH2 costs alone.